Highly Stretchable Transistors Using a Microcracked Organic Semiconductor. (17th April 2014) - Chortos, Alex; Lim, Josh; To, John W. F.; Vosgueritchian, Michael; Dusseault, Thomas J.; Kim, Tae‐Ho; Hwang, Sungwoo; Bao, Zhenan
<x xml:space="preserve">Abstract</x> Organic transistors with elastic conductors and dielectrics can be stretched up to 250% strain while maintaining the transistor characteristics. Strain‐independent properties can be achieved after an initial "programming" cycle that causes the formation of microcracks in the semiconductor. The change in mobility with strain follows the same trend in different stretching directions. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>